2019
DOI: 10.5055/jom.2019.0529
|View full text |Cite
|
Sign up to set email alerts
|

Birth outcomes with prescribed chronic and acute opioid exposure during pregnancy

Abstract: Objectives: To assess the effects of no, any, and acute and chronic prescription opioid exposure for pain during pregnancy on maternal and fetal outcomes.Design: Retrospective cohort study.Setting: Integrated healthcare delivery system. Information on pregnancies and their outcomes were obtained from administrative data and verified via manual chart review.Participants: Women ≥ 18 years of age who were pregnant between January 1, 2012 and May 31, 2015 and had chronic, acute, and no opioid exposure; defined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…7 Other studies suggested that gestational opioid exposure is associated with the risk of congenital malformations. [8][9][10] Thus, whether opioid use in pregnancy is associated with major congenital malformations remains unclear. The goal of this study was to evaluate the risk of congenital malformations associated with gestational prescription opioid exposure among pregnant women enrolled in the Rhode Island state Medicaid program.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Other studies suggested that gestational opioid exposure is associated with the risk of congenital malformations. [8][9][10] Thus, whether opioid use in pregnancy is associated with major congenital malformations remains unclear. The goal of this study was to evaluate the risk of congenital malformations associated with gestational prescription opioid exposure among pregnant women enrolled in the Rhode Island state Medicaid program.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent large cohort studies reported that prenatal opioid exposure in the first trimester is not associated with a higher risk of major congenital malformations, but codeine use during early pregnancy was associated with a higher risk of spina bifida . Other studies suggested that gestational opioid exposure is associated with the risk of congenital malformations . Thus, whether opioid use in pregnancy is associated with major congenital malformations remains unclear.…”
Section: Introductionmentioning
confidence: 99%